The North East after Brexit : impact and policy - Liddle, Joyce; Shutt, John (Emerald Publishing Limited, 2019)
The North East is one of Britain's most disadvantaged regions. This area, where wealth was generated from coal, steel and engineering during the Industrial Revolution, has struggled to progress at the same rate as regions in Southern England. With a reliance on public sector services, the North East is set to be one of the hardest hit areas after Britain's exit from the European Union. The North East after Brexit arises from new research and activities at Northumbria University to shape the future of public sector management in the region. Across a range of new themes and governance, work is focused on how public sector agencies can work better together to shape the Northern economy in the future. The North East is a key partner in the Northern Powerhouse involving three northern regions and is designed to rebalance the northern economy in the UK and bridge the chasm between north and south. This important text is set within the context of the Northern Powerhouse; a highly complex and challenging concept that demands the development of new partnerships across the regions, and the need for collaborative working across city regions in the north. With a focus on Brexit and austerity as key drivers of change, this invaluable text contributes to debates in the region surrounding employment changes and policy directions in a post- Brexit world. It will prove to be an essential read for policy makers, government researchers and those working in the fields of public sector leadership and management. Joyce Liddle is a Professor of Public Leadership and Enterprise, Director of Research and Innovation and John Shutt is a Professor of Public Policy and Management. Both are located at Newcastle Business School, Northumbria University, UK.
Keywords: Public administration -- England.; European Union -- Great Britain.; Political Science -- Public Affairs & Administration.; Public administration.; elektronické knihy; electronic books